Pengaruh Kompetensi Pedagogik dan Lingkungan Kerja Terhadap Perilaku Kerja Guru SMPN Di Kabupaten Serang Wilayah I dengan loyalitas sebagai Variabel Mediasi - Anisa Fauziyah; Yayat Ruhiat; M. Syadeli Hanafi; Cucu Atikah (Postgraduate, University of Mataram, 2025)
The study aims to describe the influence of pedagogic competence, work environment on teacher work behaviour with loyalty as mediation in SMPN Serang Regency Region I. The research used an explanatory method with a quantitative approach. The instrument used a closed questionnaire on 210 respondents using random sampling technique. The study used path analysis techniques to test the effect of independent variables on the dependent variable using lisrel. The results showed that: there is a significant positive direct effect of pedagogic competence on work behaviour with a path coefficient of 0.305, ρ value 0.00. The work environment on work behaviour has a significant positive direct effect with a coefficient of 0.50, ρ value 0.00. Loyalty to teacher work behaviour has a significant positive direct effect with a path coefficient of 0.107, ρ value 0.047. Simultaneously, it has a positive direct impact on work behaviour by 69.2%. Pedagogic competence on work behaviour through loyalty has an indirect effect but does not have a mediating effect, the sobel t value is 1.791. Similarly, the work environment on work behaviour through loyalty has an indirect effect but does not have a mediating effect with a sobel test value of 1.904.